Community engagement through Hub model approach for local consensus building for scaling agricultural recommendations at subnational levels - Van Loon, Jelle; Fonteyne, Simon; García Santiago, Jorge Octavio; Espinosa Diaz, Anabell Guadalupe; Guera, Ouorou Ganni Mariel; Ovando, Rausel; Jiménez, Benancio; May Tzun, Vladimir Nikolai; González Regalado, Jessica; Vilchis Ramos, Rodolfo; Pérez García, Mariana; García, Ana Rosa (CIMMYT, 2025)
This report documents and analyzes the implementation of a key line of work under the CGIAR Scaling for Impact (S4I) Science Program, with a focus on strengthening scaling pathways through subnational community engagement processes. The analysis draws on experiences developed during 2025 within the Hub model implemented in southern Mexico—Pacífico Sur–Oaxaca, Chiapas and the Yucatán Peninsula—and in Guatemala—Western and Eastern Hubs. Under the S4I approach, scaling is understood as an intentional, dynamic and non-linear process that connects science to territories through interactions among actors, capacities, evidence and local contexts. Within this framework, Hubs operate as territorial multistakeholder platforms, integrating participatory research, innovation, extension, capacity strengthening and network management, thereby enabling differentiated pathways to impact. The report analyzes the implementation of at least five subnational community engagement processes, designed to convene civil society, public sector and private sector actors operating in the intervention areas. These interaction spaces aim to align territorial priorities, strengthen coordination among actors and create enabling conditions for the adoption, adaptation and scaling of selected innovation or technology bundles, ensuring that the benefits of scaling are reflected directly in farmers and the communities served by local stakeholders. A central component of the analysis is the characterization of actors and the mapping of their relationships using social network analysis methods, which allows for a deeper understanding of territorial dynamics, the identification of key nodes, bottlenecks and strategic opportunities for scaling. This evidence contributes to more informed and strategic management of scaling pathways, strengthening evidence-based decision-making. The findings confirm that impact at scale does not depend solely on the availability of technical innovations, but on the quality of the social, organizational and institutional processes that accompany them. Multi-stakeholder engagement, participatory processes, capacity strengthening and technical support emerge as critical enabling factors for the sustained adoption and adaptation of innovations across diverse contexts. The analysis also highlights that there is no single pathway to scale. Hubs exhibit differentiated trajectories shaped by their agroecological, socio-economic and institutional conditions, reinforcing the need for flexible and context-responsive approaches. Recognizing and managing this diversity of pathways is essential for responsible, inclusive and sustainable scaling, in line with CGIAR principles. Overall, the report provides relevant evidence and lessons on how subnational community engagement processes, integrated within the Hub model, contribute directly to scaling processes. The results reinforce the core premise of the Scaling for Impact program: impact at scale is the outcome of intentionally designed and managed scaling pathways that connect science, actors and territories through continuous learning, multi-stakeholder coordination and evidence-based decision-making.